The Analysis Study of Diagnosis and Surgical Management of Breast Cancer : A Comprehensive Systematic Review - Anindya Ryan Pramudya; Dewandaru Istighfaris Agadinata Bramanti (The International Journal of Medical Science and Health Research, 2025)
Background: Breast cancer remains a significant global health challenge, representing the most common malignancy among women and a leading cause of cancer-related mortality. This systematic review aims to synthesize current evidence on the diagnosis and surgical management of breast cancer. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Breast cancer diagnosis and surgery have evolved with advanced imaging, molecular profiling, and oncoplastic techniques, emphasizing patient-centered care. While mastectomy remains necessary in some cases, oncoplastic approaches offer safe, effective outcomes. Future research should refine techniques, staging, and therapeutic integration.